Mangrove Biofiltration as A Green Biotechnology for Wastewater Remediation: Targeting DO, BOD, COD, Phosphate, Detergent Mbas, and Ammonia - Aini, Aini; Irawansyah, Irawansyah; Mentari, Ika Nurfajri; Maulana, Alfi; Ustiawaty, Jumari (Jurnal Biologi Tropis, 2025)
This Wastewater treatment plants are essential for reducing pollution before wastewater is discharged, but conventional systems often fail to achieve effective pollutant removal . This study aimed to measure the effectiveness of mangrove powder in treating industrial wastewater before it is discharged into the environment to improve wastewater quality. Samples were taken at two points: after conventional wastewater treatment and after treatment with mangrove biofiltration. The biofiltration system was designed to address the limitations of conventional treatment, particularly in reducing BOD₅, COD, phosphate, MBAS, and increasing dissolved oxygen (DO). Sampling was carried out using a  one liter sterile sample bottle. Sampling was carried out using a 1-liter sterile sample bottle. Sampling was carried out at one point with four repetitions. Parameters analyzed included TSS, pH, DO, BOD₅, COD, nitrate, nitrite, ammonia, phosphate, sulfate, and MBAS detergent. Mangrove biofiltration achieved reductions in TSS (55.26%), COD (99.35%), nitrate (100%), BOD₅ (99.15%), phosphate (96.67%), sulfate (99.55%), nitrite (100%), ammonia (90.00%), and MBAS (100%), while DO increased by 47.37% and pH remained stable. These improvements indicate the mangrove biofilter’s capacity to adsorb and biologically degrade organic matter and pollutants, enhancing wastewater quality to meet reuse standards. The results of the study show the potential of mangrove-based biofiltration as a solution for waste treatment units using mangrove biofiltration to reduce the concentration of DO, BOD, COD, phospat, Detergen MBAS, and Ammonis in industrial waste before being discharged into the environment.